Hydrothermal synthesis of NaTb(MoO4)2 hierarchical architectures with novel morphology and luminescence properties. Issue 15 (15th November 2016) - Jia, Guang; Tian, Jiayue; Lin, Peng; Liu, Shuang; Sun, Yan; Chen, Long; Zhang, Mengtao; Yao, Runrun; Zheng, Yuhua; Zhang, Cuimiao
Abstract: Uniform and well-dispersed NaTb(MoO4 )2 hierarchical nanoflowers have been fabricated via a hydrothermal method by using trisodium citrate as additive. The morphology and particle size of the NaTb(MoO4 )2 samples can be tuned in a controlled manner by altering the pH value of the initial solution, reaction temperature, and component of solvent. The Eu 3+ -doped NaTb(MoO4 )2 sample mainly shows the characteristic emission of Eu 3+ corresponding to 5 D0 – 7 FJ (J=1, 2, 3, 4) transitions due to an efficient energy transfer from MoO4 2− and Tb 3+ to Eu 3+ . The as-synthesized NaTb(MoO4 )2 :Eu 3+ may be applied as a novel red phosphor in optoelectronic devices or advanced flat panel displays.